KETIDAKPATUHAN TERHADAP PRINSIP GOOD CORPORATE GOVERNANCE DALAM KASUS PT JIWASRAYA: TINJAUAN HUKUM DAN IMPLIKASI BAGI PERUSAHAAN BUMN - Maria Phoebe Tjahja; Inayah Fasawwa Putri; Juan Joubert Immanuel Panelewen (LPPM Universitas Ekasakti Padang, 2023)
Good Corporate Governance is a concept that refers to the principles, regulations and practices that govern good corporate governance. GCG aims to encourage transparency, accountability, fairness, and responsibility in decision-making and company operations. The purpose of this research is to analyse non-compliance with the principles of Good Corporate Governance in the PT Jiwasraya case: legal review and implications for state-owned companies. This research method is normative juridical legal research. The result of this research is that the case of non-compliance with the Principles of Good Corporate Governance that occurred at PT Jiwasraya has a serious impact on the company, shareholders, policyholders, and other parties involved. Violations of GCG principles that occur include non-transparency of information, conflicts of interest, weak internal control systems, lack of accountability and responsibility, and weak supervision and regulation. As a State-Owned Enterprise (SOE), PT Jiwasraya should have implemented good corporate governance and GCG principles to protect the interests of stakeholders. However, it was revealed that the implementation of GCG in the company was ineffective or neglected. The PT Jiwasraya case is an important lesson on the importance of good GCG implementation and strict law enforcement in maintaining corporate integrity.